SELF-MANIPULATION AS A FORM OF DESIRE FULFILLMENT IN “CATCH ME IF YOU CAN” NOVEL BY FRANK W. ABAGNALE JR - Elfi Rahmi; Tomi Arianto (Asosiasi Ide Bahasa Kepri, 2021)
Every human being needs the need to be able to continue living one of the things that is needed is the esteem needs. This study aimed to find the esteem need from Frank William Abagnale in Catch Me If You Can novel by Frank W. Abagnale Jr. which is a real story of the main character, Frank W. Abagnale. This novel was once the best seller in New York published in 1980 which tells the story of a person who is an expert in fake checks, manipulate identities and run away to fulfill life's needs and recognition of the status, achievements and identity of a character. The theory used in this paper is based on Abraham Maslow's theory. Abraham Maslow described the needs of human life in the form of a Pyramid, where the most basic parts are the most important needs in human life. This research that used by researcher is a qualitative research. The process of presenting research results uses informal methods by describing them through words. From the process of data analysis, it can be found that the main character Frank Abagnale in the novel “Catch Me if You Can” continues to struggle to fulfill his life needs as a human. It all started from the needs of Frank who wanted to meet the needs of self-esteem and recognition from people around his environment.